Pengaruh Kosep Desain (Eksterior dan Interior), Excellent Service, dan Penetapan Harga Toko yang Bernuansa Islam Mempengaruhi Minat Belanja Konsumen Muslim dalam Kegiatan Perspektif Hukum Ekonomi Syariah - Sofiana, Fitria (Universitas Muhammadiyah Surabaya, 2018)
ABSTRACT Buying consumer interest is the seller must be able to sell a good impression has not sold the goods, the impression that can shape the image of his shop, this has been put forward by Sutisna (2001) in his book Consumer Behavior: Theory and Applications that storeatmosphere (shop atmosphere) will also determine the image of the store itself. If the store features comfortable, air-conditioned, and artistic arrangements for the use of attractive wall paint, all show that the mood of the store is able to increase the luxury and high business competitiveness. From the results of this study, the factors that influence the next decision is the excellent service (excellent service) factors that affect interest. Based on questions about comfort ditoko sakinah perceived by consumers. The service and convenience provided by the sakinah store is considered good by consumers but has not had a major impact in influencing buying interest. By providing a convenient waiting room or shofa facility for customers who are trying sakinah. Thus, customers will feel cared for and happy to re-purchase at a sakinah shop and pricing. Price determination based on the question of the respondent's price level agrees with the price paid in accordance with the quality of the sakinah product. Thus, the company must determine the price in accordance with product quality in order to compete with other companies. In addition, companies can provide discounts or discounts to attract consumers more, so as to improve purchasing decisions sakinah. From the results of this study the method used is Quantitative Design (exterior and interior) has a contribution of 63.3% together to the dependent variable (Y) ie consumer spending interest. The remaining 36.7% is influenced by other factors that are Excellent service and Price Pricing and which are not included in the research. With study research conducted in store Sakinah Wonorejo area of West Surabaya. From the store then the value of increased interest obtained the influence in forming other variables such as excellent service, pricing. Keywords: Design (exterior and interior), Excellent Service, Pricing and Interest